Loss of Asxl2 leads to myeloid malignancies in mice - Jianping Li (Nature Portfolio, 2017)
ASXL2 mutations are mostly found in a subset of leukemia patients with certain genetic aberrations; however the role of this protein in normal hematopoiesis and related malignancies is still unclear. Here the authors use a knock-out mouse model to uncover the role of Asxl2in hematopoiesis and leukemogenesis.